A world of pausabilities : an exercise in mindfulness - Sileo, Frank J., 1967- (Magination Press, an imprint of the American Psychological Association, 2017)
"Children (and adults) live in a fast-paced, demanding and stressful world. It is often difficult to slow-down our children's minds and bodies. This book was written to teach children to take a pause in their lives, to stop activity, to understand quiet time, and to think about what they are doing and where they are going"--